Effect of different inorganic filler on development of polyethersulfone mixed matrix membranes for 02/N2 separation - Mohd Khairul, Anwar Mamat (2012)
Mixed matrix membrane (MMM) is a new class of membrane materials that offers the significant potential in advancing the current membrane-based separation technology. As an attractive material that demonstrates outstanding separation properties, MMM has been the subject of worldwide academic studies conducted by many researchers especially those related to membrane technology. In this study, MMMs were prepared from polyethersulfone (PES) containing embedded with two different inorganic fillers such as zeolite 4A and carbon molecular sieve. The effect of different inorganic filler was studied in order to identify the suitable types of inorganic filler and the performance of MMM membranes. The polymer solution contains Polyethersulfone (PES) as the polymer, NMethyl Pyrrolidone (NMP) as the solvent and distilled water (14 20) as the non-solvent. The zeolite concentration valued 25 wt % was applied. To increase the compatibility of zeolite with the polymer, 3-Aminopropyl-Trimethoxysilane (APTMOS) was used to treat the zeolite prior to dope formulation to modify the zeolite surface. For both membranes, the dry/wet phase inversion method was used to produce the asymmetric flat sheet membrane. The prepared membrane was coated with silicone and N-Hexane to decrease the surface defect of the membrane. In order to determine the membrane performance, the membranes were tested using and N2 as the test gases using permeability test rig. The surface and cross section image of the prepared membrane was identified by using Scanning Electron Microscope (SEM). The results show that the MMMs with CMS had the highest selectivity of 3.61 while the zeolite MMMs selectivity is 1.44 and the optimum pressure was found at 3 bar. As a conclusion the CMS particles discussed in this paper seemingly offer several advantages over zeolites as possible molecular sieving entities for incorporation into mixed matrix membranes.